Migrasi, Kewarganegaraan, dan Partisipasi Imigran: Studi Kasus Imigran Turki di Belanda - Gusnelly S.H., M.Si. (Jurnal Kajian Wilayah, 2010)
This article focuses on transnational migration in Europe, primarily on the Turkish migrants diaspora and their citizenship participation in the Netherlands. Their migration history and its patterns are unique, thus interesting to be explored. The presence of the Turkish migrants has enriched the ethnic diversity in the European Society, including the Dutch. They seek for acknowledgement in their host country through citizenship, to gain various accesses from the local government to the European society in general. The basic analyses of the paper based on empirical studies on the Turkish migrants. The questions posed in this article are (1) what is the importance of being European citizen and why are they applying the Dutch citizenship? (2) How is the relationship between the Turkish migrants and the Dutch government especially to gain various accesses from local government? To answer these questions, the article will explore the history and motivation of the Turkish, interaction between the Turkish migrants and the native society, and how they interact with other ethnic groups, local institution and government. These would lead to the discussion about the participation of the Turkish migrants on the public spheres.Keywords: transnational migration, Turkish migrants, integration, Dutch citizenship